The determinants of hospital length of stay in Nigeria - Conrad Y. Puozaa (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose- Hospital length of stay (LOS) does not only signal the seriousness of illness, it can also lead to catastrophic cost for patients or households. This paper examines the factors that determine LOS in Nigeria; a country where more than 99% of the cost of health care is borne by patients. Design/methodology/approach- The dataset, consisting of 1,150 people who reported one or more overnight stays in a hospital, comes from the two waves of the Nigerian General Household Survey. Due to the overdispersion and the truncation of LOS at zero, a zerotruncated negative binomial regression model was adopted to establish the causal relationship between LOS and patients' predisposing, enabling and needs-related characteristics. Findings- LOS tends to increase with the following factors: age, household size, availability of formal medical care facilities, and the severity of illness. However, there is an inverse relationship between LOS and the cost of care, being a female, resource endowment in the area, and utilization of preventive care. People in lower and higher socioeconomic brackets tend to have higher LOS than people in the middle socioeconomic bracket. Research limitations - Actual description of diseases respondents suffered from, which is important in determining the severity of illness, was not available. I relied on a proxy to measure the severity of illness. Implications- Policy makers in developing countries continue to explore strategies for reducing poverty and vulnerabilities among the populace. An understanding of the determinants of LOS can help inform policymakers, hospital administrators and patients regarding health care reforms, planning for patients LOS, and planning for the period of hospitalization, respectively. Originality/value- To the best of my knowledge, this is the first paper to empirically examine the determinants of LOS in Nigeria.
Keywords: I12; I28; 330; Hospital Length of Stay; Zero-truncated Negative Binomial; Healthcare Reforms; GHS-Panel; Nigeria